الضغط الضريبي كحافز للتهرب والغش الضريبي - رحال, نصر; موفق, سهام (جامعة الوادي - University of Eloued, 2018)
ن فرض الضرائب على المكلفين يجب أن يكون منطقيا حتى يكون ذلك مقبولا لديهم ولو أفرطت السلطات في رفع مستوى معدلات الضرائب والرسوم ستكون النتيجة الحتمية وهي نقص الحصيلة الضريبية، بل يتعدى ذلك إلى تغير سلوك المكلفين فبدل من انتهاج سلوك التصريح والتسديد العادي في الآجال القانونية، سوف يتجهون نحو ممارسة التهرب والغش الضريبي هربا من الضغط الضريبي المفروض عليهم. Taxation on taxpayers must be reasonable in order to be acceptable to them. Even if the authorities increase the level of tax and duty rates, the inevitable result will be a lack of tax revenues, but rather a change in the behavior of the taxpayers. Are moving towards the practice of evasion and tax fraud to escape the tax pressure imposed on them. Therefore, this research paper clarifies the conceptual framework for tax evasion and fraud, as well as the presentation of tax pressure theory
Tax pressure as an incentive for evasion and tax fraud
مقال
Keywords: التهرب الضريبي، الغش الضريبي، الضغط الضريبي; Tax evasion, tax fraud, tax pressure